Lotion Formulation with Papaya Seed Extract (Carica Papaya L) as a Skin Moisturizer - Syarifuddin, Aminah; Juliana, Iga (Jurnal FARMASIMED (JFM), 2024)
Papaya seeds (Carica papaya L) have many vitamin contents that function to help increase immunity, fight free radicals, and also help increase skin moisture. Lotion is one of the pharmaceutical preparations in the form of beauty products that function to brighten and help increase skin moisture. In this research, a formulation of papaya seed extract will be made to become a lotion preparation that can increase skin moisture. This study tested the effectiveness of the preparation on the skin of volunteers. This study was conducted by making papaya seed extract through a maceration process using 96% ethanol, the extract was formulated in a lotion preparation in various concentrations. The resulting lotion was tested for homogeneity, pH, organoleptic, moisture and irritation on volunteers. Treatment was carried out for three days using lotion once a day. Lotion with a concentration of 3%, 5% and 7% which was homogeneous with a blank pH of 5.64, a 3% formulation pH of 5.84, a 5% formulation pH of 5.72, and a 7% formulation pH of 5.95 was found to not irritate the skin of volunteers, stable in room temperature storage. The results of the humidity test on Blanko were 43.3%, 3% formulation 45.2%, 5% formulation 49.95, 7% formulation 52.45%, and comparator 41%. The best result of the humidity test was formulation 3 with a concentration of 7% with an average value of 52.45%. Papaya seed extract can be formulated as a lotion preparation because it meets the physical test requirements of the preparation which shows that the preparation is homogeneous, the pH is stable during storage at room temperature, and does not irritate the skin. The papaya seed extract lotion preparation with a concentration of 7% provides a better humidity level effect compared to Blanko, F1 (3%), F2 (5%), F3 (7%) and also the comparator preparation.